A substitute for substitution: Bolsa Família's effects on the combination of work and school for children and adolescents aged 10 - 18 - Fernando Gaiger Silveira; Ross van Horn; Bernardo Campolina (International Policy Centre for Inclusive Growth (IPC-IG), 2013)
This study seeks to examine specifically the extent to which the benefit has affected the allocation of time between school and work by children and adolescents. The study takes into account that, in Brazil, it is possible and likely to combine study and work, since the vast majority of schools operate in shifts. We return to this point in our analysis. On the one hand, it can be argued that the programme has beneficial effects on children's time allocation if it increases school attendance and time devoted to studying and reduces working time. The programme can also be seen as having beneficial effects if it hinders or prevents an increase in the number of working hours, given the strictness in the time devoted to school. In the former case, it is expected that one will observe, simultaneously, an increase in the time devoted to studying and a decline in labour market participation. In the latter, one can observe greater dedication to school without, however, resulting in a decline in labour market participation. Some studies that have reviewed the programme effects on schooling and labour market decisions show a positive effect on school attendance, as well as a decrease in labour market participation, while others show only increased school attendance, without any reduced labour market participation. Taking a middle ground, the results from this paper show that the programme has positive effects on school attendance, but instead of having a negative or insignificant effect on labour market participation, the programme effect simultaneously increases the likelihood of working. We discuss these results in five sections.
Keywords: 330